Persuasion eaudiobook - Austen, Jane (Recorded Books Inc., 1984)
A story of the love between upper-class Anne Elliott and Captain Wentworth, who must earn his fortune. Set against the rarefied sensibilities of the upper-class England of Austen's day, the novel is both a satire upon class values and differences, and an engaging story.